Formation of zirconia precursor nanoplates mediated by ionic liquid and transformation to monoclinic ZrO2 nanostructures - Tian, Pei; Lin, Hechun (International journal of materials research, 2018)
The [Zr(OH) imidazolium complex was used to synthesize a zirconia precursor with plate-like nanostructue hydrolyzed under strong acid conditions, which was characterized by means of powder X-ray diffraction, thermogravimetric-differential scanning calorimetry, Fourier transform infrared spectroscopy, Raman spectroscopy, elemental analysis, inductively coupled plasma and electronic differential system. The zirconia precursor can be transformed to monoclinic ZrO by annealing at a temperature above 400 °C. With the increasing of the curing temperature, it tended to give rise to porous ZrO nanostructures.